Parasitological evidence for specialized foraging behavior in lake-resident Arctic char ( Salvelinus alpinus ) - Curtis, Mark A.; Bérubé, Michel; Stenzel, Andreas (Canadian Journal of Fisheries and Aquatic Sciences, 1995)
Analyses of statistical associations between the stomach contents and endoparasites of Arctic char, Salvelinus alpinus, from a small (9 ha) lake in northern Quebec revealed that food items found in fish stomachs at the time of capture frequently consisted of intermediate hosts for the parasites infecting the fish. Thus the stomach contents of Arctic char infected by Diphyllobothrium ditremum, D. dendriticum, and Eubothrium salvelini tended to include copepods, while fish infected by the digenean Crepidostomum farionis more frequently contained insect larvae (ephemeropterans) and fish infected by the acanthocephalan Echinorhynchus lateralis most often had amphipods in their stomachs. Moreover, strong quantitative associations were evident between parasites utilizing intermediate hosts from either the benthic or the limnetic zone of the lake. This suggests that some degree of persistent feeding specialization was present among members of the Arctic char population over an extended period of time, with individual fish predominantly feeding upon prey organisms in either limnetic or benthic habitats. In this manner an allopatric Arctic char population may function analogously to more diverse fish communities, where specialist foraging behavior is developed to most efficiently exploit the food web.